Factor Analysis Of The Influence Of Creativity And Product Innovation On Consumer Satisfaction On Handycraft Products, Bandung City - Henry Meytra Taufik; Dwizha Khairinisya (Enrichment : Journal of Management, 2022)
Bandung is a tourism city with a wide variety of handicraft products that attract tourists. This study aims to determine the relationship between creativity and product innovation on consumer satisfaction of generation Z and millennials. In this study, 110 questionnaires were distributed online to consumers in the city of Bandung, West Java. The data obtained were then processed using multiple regression analysis with the help of SPSS 25 software. The results of this study indicate that there is a direct influence between creativity and consumer satisfaction. In addition, product innovation was also found to have an effect on consumer satisfaction. The results in this study obtained a score of 54.2%, this score indicates that there is an influence between the variables of creativity and product innovation on customer satisfaction. This study is proposed to emphasize the importance of creativity and innovation skills in product development, especially in the handicraft industry in the city of Bandung